2018
DOI: 10.1080/10903127.2017.1376135
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Versus Longer Shift Durations to Mitigate Fatigue and Fatigue-Related Risks in Emergency Medical Services Personnel and Related Shift Workers: A Systematic Review

Abstract: The quality of existing evidence on the impact of shift duration on fatigue and fatigue-related risks is low or very low. Despite these limitations, this systematic review suggests that for outcomes considered critical or important to EMS personnel, shifts <24 hours in duration are more favorable than shifts ≥24 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 58 publications
2
46
0
1
Order By: Relevance
“…Our study is one of the largest prospective studies of air‐medical clinician alertness in relation to shift duration . We detected no differences in sleep behavior/patterns before and after shifts by shift duration.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Our study is one of the largest prospective studies of air‐medical clinician alertness in relation to shift duration . We detected no differences in sleep behavior/patterns before and after shifts by shift duration.…”
Section: Discussionmentioning
confidence: 53%
“…Similar research on other healthcare shift worker populations (eg, resident physicians) has shown a progressive degeneration in performance and cognitive performance in relation to extended shift work . Several studies have investigated the relationship between shift duration and alertness of air‐medical clinicians . Braude et al investigated the impact of shiftwork cognitive performance in a small air‐medical system with 22 air‐medical participants .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations